Effect of fiber surface treatment of poultry feather fibers on the properties of their polymer matrix composites. Issue 2 (30th July 2012) - Huda, M. S.; Schmidt, W. F.; Misra, M.; Drzal, L. T.
Abstract This study develops the enabling technology needed to transform the fibers of poultry feather (FPF), a waste product left over after processing poultry in the food processing industry, as reinforcement filler material for manufacturing composite materials. We successfully fabricated composite materials from biopolymers (polylactide, PLA) and FPF that were produced by the extruder system. FPF‐reinforced polypropylene (PP) composites were also compounded and molded and compared to PLA/FPF composite. The composites were evaluated via thermal and mechanical analysis. To enhance the adhesion between the polymer matrix and the FPF, the FPF have been treated with sodium hydroxide, 10% maleinized polybutadiene rubber, and a silane‐coupling agent. X‐ray photoelectron spectroscopy was used to analyze the influence of modifications on the properties of fibers and found that the coupling agent was localized at the surface of the fibers. Thermal behavior of pretreated fibers was also studied by thermogravimetric analysis. All treatments clearly enhanced thermal performance of fibers. This enhancement of fiber properties, along with an improvement in fiber/matrix adhesion, led to improvement in the mechanical properties of the composite materials. It was found that the surface‐treated fiber‐reinforced materials offered superior mechanical properties compared to untreated fiber‐reinforced composite materials. Moreover, morphological studies by the scanning electron microscopy demonstrated that better adhesion between the fiber and the matrix was achieved especially for the surface‐treated fiber‐reinforced composite materials. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013